Akuntansi Syariah di Indonesia dalam Era Digital - Rahmawati, Yunaita (Institut Agama Islam Sunan Giri Ponorogo, 2022)
Along with technological advances, indirectly the existing system of sharia-based accountants is also forced to follow the revolution. This is because humans are very dependent on technology in carrying out their daily activities. Life in accounting such as reading, recording, and calculating is now starting to be transferred to technology. This study tries to find out how the influence of digitalization on Islamic accounting in Indonesia, and also find out whether digitalization is an opportunity and a challenge for the Islamic accounting profession and how to prepare accounting students in the digitalization era. The results indicate that digitalization has an influence on the growth of sharia-based accounting, especially in Indonesia. In addition to the influence of digitalization on sharia accounting in Indonesia, digitalization also brings opportunities as well as challenges for the accounting profession, especially sharia-based accountants. Opportunities for a new profession where accountants' human resources can compete with the presence of technology. However, this will also be a challenge for accountants, with technology that will take over the role of accountants, indirectly reducing the accounting profession in the world of work will be eliminated and replaced by technology. Therefore, there is a need for a response that every accountant must have to deal with accountants in the future. This then becomes a challenge for agencies that have to produce and produce a generation of accountants who are superior in their fields and are also technologically literate. With the renewal system in the curriculum of the teaching and learning process that is adapted to the needs of the times, it is hoped that this will give birth to a generation of sharia-based accountants who are ready to compete in the digitalization era. That way digitalization will be an extraordinary job prospect in the field of sharia-based accountants.